PENGARUH TEKANAN WAKTU TERHADAP KINERJA AUDITOR: WHISTLEBLOWING INTENTION SEBAGAI VARIABEL PEMODERASI - CrusytaDewi, Putu Sita; Merkusiwati, Lely Aryani (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The performance of auditors is a critical component in generating good audit quality. The purpose of this study are determine the effect of time pressure on the auditor performance with whistleblowing intention as moderating variabel. The study was conducted on the public accounting firm in the province of Bali. Research samples were obtained by 35 external auditors who work on the public accounting firm in the province of Bali  with nonprobability sampling methods and saturated sampling technique. Technique of data analysis is moderated regression analysis. The results showed that time pressure has negative effect to auditor performance. Whistleblowing intention to weaken the negative effect of time pressure on the performance of auditors.
Keywords: Time Pressure, Whistleblowing Intention, Auditor Performance